Analisis Penetapan Cagar Budaya Kampung Adat Cikondang Sebagai Sarana Konservasi Hutan Adat - Alfiah Rahmawati; Tri Cahyanto (Pusat Riset dan Inovasi Nasional, 2024)
Indonesia is a country with diverse cultures, and these cultures need to be preserved, one way being through Law No. 11 of 2010 on Cultural Heritage. The traditional village of Cikondang in West Java has been designated as cultural heritage, which has a significant impact on the preservation of its customary forest. This study aims to analyze the impact of this designation on the conservation of the Customary Forest. Using a qualitative method, the research was conducted through interviews, observations, and literature studies. The results show that the designation as cultural heritage strengthens the protection, management, and preservation of the customary forest, which serves as a water reservoir, a habitat for flora and fauna, as well as a center for education and research. Strict customary regulations, such as restrictions on entering the forest on certain days and the use of resources only for customary purposes, help maintain the sustainability of the ecosystem. The designation as cultural heritage also boosts tourism and the economic well-being of the local community. Thus, the preservation of the customary forest in the traditional village of Cikondang is not only rooted in local wisdom but also reinforced by national legal policies, which overall support the sustainability of the ecosystem and the welfare of the local community. ,